Obesity modulates the cellular and molecular microenvironment in the peritoneal cavity: implication for ovarian cancer risk - Shea, Amanda A.; Heffron, Connie Lynn; Grieco, Joseph P.; Roberts, Paul C.; Schmelz, Eva M. (Frontiers in Immunology, 2024)
Abdominal obesity increases the risk of developing ovarian cancer but the molecular mechanisms of how obesity supports ovarian cancer development remain unknown. Here we investigated the impact of obesity on the cellular and gene expression profiles of distinct abdominal tissues, focusing on the peritoneal serous fluid (PSF) and the omental fat band (OFB) as critical determinants for the dissemination of ovarian metastases and early metastatic events within the peritoneal cavity. Other peritoneal adipose tissues including parametrial and retroperitoneal white adipose tissues were also investigated. The cellular composition of abdominal tissues and changes in gene expression were evaluated by flow cytometry and qPCR RT2-profiler PCR arrays and qRT-PCR, respectively. While limited effects were observed in the other peritoneal adipose tissues, feeding C57BL/6 mice a high-fat diet (HFD) led to distinct changes in the PSF and the OFB: a depletion of B cells but an increase in myeloid-derived suppressor cells (MDSC) and mono/granulocytes, generating pro-inflammatory environments with increased expression of cyto-and chemokines, and genes supporting adhesion, This is a provisional file, not the final typeset article survival, and growth, as well as suppression of apoptosis. This was associated with a higher peritoneal tumor burden compared to mice fed a low-fat diet (LFD). Changes in cellular and genetic profiles were often exacerbated by the HFD. There was a large overlap in genes that were modulated by both the HFD and the cancer cells, suggesting that this 'genetic fingerprint' is important for ovarian metastases to the OFB. In accordance with the 'seed and soil' theory, our studies show that obesity contributes to the generation of a pro-inflammatory peritoneal environment that supports the survival of disseminating ovarian cancer cells in the PSF and the OFB and enhances the early metastatic adhesion events in the OFB through an increase in fibronectin1, collagen I, and Tenacin C expression as well as in genes supporting growth and invasion. The identified genes could potentially be used as targets for prevention strategies to lower the ovarian cancer risk in obese women.